RECONTEXTUALIZING EFL READING INSTRUCTION THROUGH LOCAL WISDOM: A MIXED-METHODS STUDY OF PROBLEM-BASED LEARNING - Lanlan Muhria; Sri Wuli Fitriati; Suwandi Suwandi; Sri Wahyuni (Universitas Labuhanbatu, 2026)
Purpose – This study investigates how recontextualizing EFL reading instruction through local-wisdom-based Problem-Based Learning (PBL) supports students’ reading comprehension and learning experiences.Methodology – The study employed an explanatory sequential mixed-methods design to integrate students’ perceptions with their classroom experiences. Quantitative data were collected through a closed-ended Likert-scale questionnaire administered to 27 third-semester English Language Teaching (ELT) students, examining perceived support for reading comprehension across text understanding, inferential reading, critical reading, cultural relevance, and engagement. Qualitative data were gathered through three classroom observations, reflective journals, and in-depth interviews with three purposively selected students.Findings – Students perceived strong support for reading comprehension, particularly in cultural relevance, understanding main ideas, and engagement. Qualitative evidence indicates that familiarity with local narratives, traditions, and places reduced cognitive distance between texts and readers, enabling more focused meaning construction in English. Problem-based tasks further positioned reading as a purposeful, collaborative activity focused on solving contextualized problems rather than answering isolated comprehension questions. However, support for inferential and critical reading was perceived more unevenly, reflecting differences in linguistic readiness and analytical confidence. Integration of quantitative and qualitative findings demonstrates that positive perceptions of reading support were grounded in culturally familiar, problem-oriented, and socially mediated reading experiences.Contribution – The study concludes that local-wisdom-based PBL fosters a coherent EFL reading environment that anchors comprehension and engagement while gradually supporting the development of higher-order reading processes.